Flexible terahertz optics: light beam profile engineering via C-shaped metallic metasurface - Ivaškevičiūtė-Povilauskienė, Rusnė; Čižas, Vladislovas; Nacius, Ernestas; Grigelionis, Ignas; Redeckas, Karolis; Bernatonis, Matas; Orlov, Sergej; Valušis, Gintaras; Minkevičius, Linas (Frontiers in Physics, 2023)
The potential of terahertz (THz) imaging implementation in a large variety of applications requires compact, reliable, and relatively low-cost solutions in systems constituents. Here we focus on the development of passive optical elements and demonstrate flexible and reliable THz beam profile engineering for imaging aims via mechanical bending of a stainless steel-based C-shaped metasurface. The designed and laser-ablation technology fabricated metasurface provides compact THz focusing and enables THz light engineering as well as polarization control ability in THz imaging. Focusing, light profile engineering, and polarization control performances of the metasurfaces with different focal distances and C-shape designs are presented. Experimental data are well supported by simulations, using Finite Difference Time Domain (FDTD) method. THz images of different objects at 94 GHz using InP Gunn diode, bow-tie sensors, and exclusively metasurfaces-based optics are exposed. Further routes in the development of low-cost multicolor and polarization-sensitive THz imaging are discussed.